Growth faltering or deceleration toward target height: Linear growth interpretation using WHO growth standard 2006 for Indonesian children - Annang Giri Moelyo; Mei Neni Sitaresmi; Madarina Julia (PLoS ONE, 2025)
Objective When referred to the WHO Growth Standards 2006, children in many developing countries showed growth faltering in childhood. A previous study showed that the faltering affected the whole population, not only the disadvantaged ones. We aimed to look for an alternative explanation for this universal decline in length or height-for-age z-scores (HAZ), as lengths/ heights of Indonesian children were compared to the WHO growth standard 2006: Is it a faltering of growth or is it a deceleration toward target height. Methods We used data on age, gender, height, BMI, parental height and education, household socioeconomic status, and place of residence of children <  5 years old collected by the Indonesia Family Life Survey (IFLS) in 1993, 2000, 2007, and 2014. HAZ was calculated according to the WHO 2006 growth standard. Target heights were calculated from parental heights and converted to target height z-scores (THz). Discrepancies between the two values were used to show the children’s growth patterns in relation to their target heights across ages. Results The study included 11,241 parent-child pairs from four surveys. At birth, infants were around 1.50 z-scores longer than their THz. However, at two years of age, the discrepancies were almost zero. At 2–5 years old, the discrepancies stayed at the same level. The patterns were similar regardless of the position of the target heights among the height distribution, at the upper or the lower part. Conclusion We observed a deceleration toward target height, not growth faltering, in the first two years of life of Indonesian children when the WHO Growth Standard 2006 was used as the reference.